Heart rate variability and the relationship between trauma exposure age, and psychopathology in a post-conflict setting - Liddell, Belinda J. (BMC Psychiatry, 2016)
BACKGROUND: Cumulative exposure to potentially traumatic events (PTEs) increases risk for mental distress in conflict-affected settings, but the psychophysiological mechanisms that mediate this dose-response relationship are unknown. We investigated diminished heart rate variability (HRV) – an index of vagus nerve function and a robust predictor of emotion regulation capacity - as a vulnerability marker that potentially mediates the association between PTE exposure, age and symptoms of posttraumatic stress disorder (PTSD), psychological distress and aggressive behavior, in a community sample from Timor-Leste — a post-conflict country with a history of mass violence. METHOD: Resting state heart rate data was recorded from 45 cases of PTSD, depression and intermittent explosive disorder (IED); and 29 non-case controls. RESULTS: Resting HRV was significantly reduced in the combined case group compared with non-cases (p = .021; Cohen’s d = 0.5). A significant mediation effect was also observed, whereby a sequence of increased age, reduced HRV and elevated PTSD symptoms mediated the association between PTE exposure and distress (B = .06, SE = .05, 95 % CI = [.00–.217]) and aggression (B = .02, SE = .02, 95 % CI = [.0003–.069])). CONCLUSION: The findings demonstrate an association between diminished resting HRV and psychopathology. Moreover, age-related HRV reductions emerged as a potential psychophysiological mechanism that underlies enhanced vulnerability to distress and aggression following cumulative PTE exposure.